Helmet for my pillow : from Parris Island to the Pacific - Leckie, Robert, 1920-2001.; Nelson, John Allen, 1959- ([Old Saybrook, Conn.] : Tantor Audio, 2010)
Follow John Leckie's odyssey, from basic training on Parris Island, South Carolina, all the way to the raging battles in the Pacific, where some of the war's fiercest fighting took place. Recounting his services with the 1st Marine Division and the brutal action on Guadalcanal, New Britain and Peleliu, Leckie spares no detail of the horrors and sacrifices of war.
Title from web page.
Unabridged.
Compact discs.
Read by John Allen Nelson.
Keywords: Leckie, Robert, -- 1920-2001.; United States. -- Marine Corps; World War, 1939-1945 -- Personal narratives; World War, 1939-1945 -- Naval operations; World War, 1939-1945 -- Campaigns -- Pacific Ocean; Audiobooks